2005
DOI: 10.1029/2004jc002578
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐up and the effects of a submarine canyon: Applications to upwelling in Astoria Canyon

Abstract: [1] A parameterization for the on-shelf mass flux induced by upwelling through a shelf break submarine canyon is estimated by laboratory spin-up experiments. We determine the effects of a submarine canyon on flow evolution implicitly by measuring the topographic drag force in the context of a heuristic model. Trials were performed across a range of values for the shelf break velocity, Coriolis frequency, and buoyancy frequency. Assuming the drag force within the canyon is balanced locally by rotation, we propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…Various previous laboratory and numerical studies explored the interaction of either steady or oscillatory flows (mimicking the passage of coastally trapped waves) with a submarine canyon (Klinck 1996;Codiga et al 1999;She and Klinck 2000;Pé renne et al 2001a,b;Allen et al 2003;Boyer et al 2004;Mirshak and Allen 2005;Haidvogel 2005;Kä mpf 2006Kä mpf , 2007. In agreement with the field observations reported by Hickey (1997), these studies found a pronounced asymmetry of canyon-flow interaction depending on the direction of the incident flow.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Various previous laboratory and numerical studies explored the interaction of either steady or oscillatory flows (mimicking the passage of coastally trapped waves) with a submarine canyon (Klinck 1996;Codiga et al 1999;She and Klinck 2000;Pé renne et al 2001a,b;Allen et al 2003;Boyer et al 2004;Mirshak and Allen 2005;Haidvogel 2005;Kä mpf 2006Kä mpf , 2007. In agreement with the field observations reported by Hickey (1997), these studies found a pronounced asymmetry of canyon-flow interaction depending on the direction of the incident flow.…”
Section: Introductionsupporting
confidence: 62%
“…For steady upwelling-favorable ambient flows, previous studies (Kä mpf 2007) suggest that the onshore transport of dense water through a shelfbreak canyon varies quadratically with the speed of the incident flow U and is inversely proportional to the Brunt-Vä isä lä frequency N. On the basis of laboratory spinup experiments, Mirshak and Allen (2005) proposed a parameterization in which onshore transport of dense water was proportional to U 8/3 /N, which is not too different from Kä mpf's result. Predicted net transports, however, appeared to be underestimated by one order of magnitude in comparison with numerical findings and observational evidence (see Kä mpf 2007).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Dependency of vertical velocity to one over the Brunt-Väisälä frequency has been found in laboratory experiments (Boyer et al, 2004;Mirshak and Allen, 2005) and numerical models (Kämpf, 2007) or to one over the square of the Brunt-Väisälä frequency (Haidvogel, 2005). Due to the importance of advection, the total flux through the canyon increases more quickly than the along-shelf velocity: for upwelling, using laboratory model, to the 8/3 power (Mirshak and Allen, 2005) or using a numerical model, squared (Kämpf, 2007). For oscillatory flow the total flux through the canyon is proportional to the velocity squared (Haidvogel, 2005).…”
Section: Canyon-driven Upwelling/downwellingmentioning
confidence: 99%
“…Boyer et al, 1991;Perenne et al, 2001a;Boyer et al, 2006) have clearly shown net upwelling over the canyon. Models of upwelling episodes over canyons have been used both to estimate upwelling flux through a canyon (Mirshak and Allen, 2005) and to test numerical models (Perenne et al, 2001a;Allen et al, 2003). Laboratory models are limited by the size they can be built and thus the maximum Reynolds number that can be modelled.…”
Section: Laboratory Models Of Upwelling/downwelling In Canyonsmentioning
confidence: 99%